Digitalization as a component of anti-crisis management at the macro-, meso-, and micro-levels of the economic systems functioning - Khatser, Maksim; Polusmiak, Leonid (Management and Entrepreneurship: Trends of Development, 2024)
The article is devoted to the formation of new scientific solutions regarding the digitalization study as a component of anti-crisis management at the macro- (state), meso- (region of the country, industry), micro- (subject of entrepreneurial activity) functioning of economic systems in Ukraine. The scientific and practical necessity of accelerating the digitization of anti-crisis management in the country has been revealed. The aim of the article is the theoretical characterization of digitization as a component of anti-crisis management at the macro- (state), meso- (region of the country, industry), and micro- (subject of entrepreneurial activity) functioning of economic systems in Ukraine. Methodology: a complex of general and special methods has been used at the empirical and theoretical levels, such as the method of literary analysis to determine the essence of the terms “digitalization” and “digitalization of anti-crisis management”; the abstraction method for determining the key elements of digitization as a component of anti-crisis management for various levels of economic systems functioning; methods of analysis and synthesis to determine the place and role of digitization in anti-crisis management for different levels of economic systems functioning; methods of induction and deduction to determine the positive and negative sides of the digitalization process of anti-crisis management, and to provide a theoretical characterization of digitalization as a component of anti-crisis management for different levels of economic systems functioning. Methods of systematization, grouping, and logical generalization for systematization of information, conclusion formation, and scientific proposals of the article have also been implied. The article uses system and functional, historical, and systemic approaches to reveal and solve the problems of providing a theoretical characterization of digitalization as a component of anti-crisis management for various levels of economic systems functioning in Ukraine. Results: a theoretical characterization of digitalization as a component of anti-crisis management at the macro- (state), meso- (region of the country, industry), and micro-levels (subject of entrepreneurial activity) of economic systems functioning in Ukraine has been provided. JEL Classification: D21, М 21, Р 50